STRATEGI COPING STRES PENDERITA DIABETES MELLITUS DENGAN SELF MONITORING SEBAGAI VARIABEL MEDIASI - Muhammad Jamaluddin, M.Si (El-QUDWAH, 2008)
Diabetes is a health problem which attacks to almost all linings of world societies. Diabetes can not heal totally, therefore, what is needed is just a good treatment towards the disease both physically (by controlling blood sugar level and eat pattern) and psychologically (by controlling emotion, feeling of depress or stress) since the impact of this disease is also both physically and psychologically. This research is aimed to reveal the correlation between diabetes stress and coping strategy with self monitoring as the mediation variable of the diabetes patients in Public Regional Hospital of Yogyakarta Region. This research consists of one dependent variable, that is, diabetes stress and one independent variable, that is, coping strategy and, one mediation variable, that is, self monitoring. The data collection is conducted using the scale method. The subjects of this research are forty two diabetes patients in Public Regional Hospital of Yogyakarta Region. The data analysis used is the path analysis. The findings of this research show that there are no significant correlations between diabetes stress and coping strategies with self monitoring as the mediation variable with beta = 0.230, -0.127, 0.143, and p 0.050. Furthermore, there also no significant correlations between the coping strategy and the stress of diabetes patients with beta of = 0.230, t = 1.470, and p = 0.150. Self monitoring was correlates insignificantly to the diabetes stress with beta of = -0.127, t = -0.811, and p = 0.422. Keywords: Diabetes Stress, Coping Strategy, Self Monitoring.